TRI PARARTHA SEBAGAI LANDASAN MENCIPTAKAN EKOSISTEM PENDIDIKAN HUMANIS DI IAHN TAMPUNG PENYANG PALANGKA RAYA - Putu Cory Candra Yhani; Ni Kadek Supadmini (Guna Widya: Jurnal Pendidikan Hindu, 2025)
The doctrine of Tri Paraartha, encompassing the values of Asih (compassion), Punia (altruistic generosity), and Bhakti (devotional service), serves as a philosophical foundation for developing a humanistic educational ecosystem at IAHN Tampung Penyang Palangka Raya. This study aims to examine the implications of integrating Tri Paraartha values through a humanistic approach to foster holistic character development in students, covering intellectual, emotional, social, and spiritual dimensions. Employing a qualitative descriptive method, this research synthesizes textual analyses of Hindu scriptures and scholarly literature on humanistic education theory. The findings reveal that the application of Tri Paraartha strengthens students' empathy, altruism, and devotion, thereby enhancing moral reasoning, promoting social cohesion, and fostering emotional resilience. Specifically, Asih nurtures compassionate interpersonal relationships, Punia cultivates social responsibility and equilibrium, and Bhakti instills a deep commitment to service, both to the divine and to the community. Integrating these values into the educational process not only fortifies individual morality but also promotes the development of an inclusive, harmonious, and ethically grounded learning environment. Therefore, the implementation of Tri Paraartha through a humanistic educational approach is critical in producing adaptive, character-driven Hindu generations capable of making meaningful contributions to a dignified and civilized global society